OBSERVING AND PRODUCING DURATIONAL HAND GESTURES FACILITATES THE PRONUNCIATION OF NOVEL VOWEL-LENGTH CONTRASTS - Li, Peng; Baills, Florence; Prieto, Pilar (Studies in second language acquisition, 2020)
While empirical studies have shown the beneficial role of observing and producing hand gestures mimicking pitch features in the learning of L2 tonal or intonational contrasts, mixed results have been obtained for the use of gestures encoding durational contrasts at the perceptual level. This study investigates the potential benefits of horizontal hand-sweep gestures encoding durational features for boosting the perception and production of nonnative vowel-length contrasts. In a between-subjects experiment with a pretest–posttest design, 50 Catalan participants without any knowledge of Japanese practiced perceiving and producing minimal pairs of Japanese disyllabic words featuring vowel-length contrasts in one of two conditions, namely with gestures or without them. Pretest and posttest consisted of the completion of identical vowel-length identification and imitation tasks. The results showed that while participants improved equally at posttest across the two conditions in the identification task, the Gesture group obtained a larger improvement than the No Gesture group in the imitation task. These results corroborate the claim that producing hand gestures encoding prosodic properties of speech may help naïve learners to learn novel phonological contrasts in a foreign language.